Multiplication operator on a matrix polynomial - Mikityuk , Ya. V.; Al-Tunzhi , M. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
It is proved that the study of a perturbed multiplication operator on a matrix polynomial in the space L_2 (R, C^n) may be reduced to the study of a perturbed multiplication operator with independent variable in the space L_2 (R, ω, C^N) with weight ω satisfying the Mackenhaupt condition.